The Role of Jabatan Agama Islam Pahang (JAIP) in Da'wah Activities With Reference to Orang Asli of Jerantut, Lipis and Jengka - Ida Hayani Bt Mohamed Idris (Universiti Sains Islam Malaysia, 2011)
This research was done to study the role of Jabatan Agama Islam Pahang (JAIP) in da'wah and educating Orang Asli in the state of Pahang. The objective of this research was to identify the programs that had been organised and planned by JAIP in order to attract Orang Asli towards Islam. The research subjects were Orang Asli from district of Jerantut, Kuala Lipis and Jengka. This research is a field research. In gathering the data and information needed to complete this research, many methods had been used including interviews and library research. From this research, it was found that all the programs that provided and organized by JAIP had been successfully implemented. As a result, many of Orang Asli had converted to Islam. Therefore, the Da'is from JAIP must increase their effort by carry out the task more aggressive and efficient to attract more Orang Asli to convert to Islam. Besides that, the public has an obligation to help JAIP in every program because their participation in the programs will help to increase the chance of attracting Orang Asli to convert to Islam and also it also the pinpoint of the success of the programs.